A Quantified Past: Toward Design for Remembering With Personal Informatics. (1st November 2016) - Elsden, Chris; Kirk, David S.; Durrant, Abigail C.
Abstract : This article questions how people will interact with a quantified past —the growing historical record generated by the increasing use of sensor-based technologies and, in particular, personal informatics tools. In a qualitative study, we interviewed 15 long-term users of different self-tracking tools about how they encountered and made meaning from historical data they had collected. Our findings highlight that even if few people are self-tracking as a form of deliberate lifelogging, many of them generate data and records that become meaningful digital possessions. These records are revealing of many aspects of people's lives. Through considerable rhetorical data-work, people can appropriate such records to form highly personal accounts of their pasts. We use our findings to identify six characteristics of a quantified past and map an emerging design space for the long-term and retrospective use of personal informatics. Principally, we propose that design should seek to support people in making account of their data and guard against the assumption that more, or "better, " data will be able to do this for them. To this end, we speculate on design opportunities and challenges for experiencing, curating, and sharing historical personal data in new ways.